Strengthening Participatory Governance: Dynamics of Citizen Group Engagement in Village Budget Policy Formulation in Dua Boccoe Village - Muslimin Muslimin (Universitas Cahaya Prima, 2025)
Community participation is a fundamental element of good governance and sustainable rural development. This community engagement program aimed to strengthen citizens’ participation in village planning and budgeting processes in Desa Dua Boccoe through participatory approaches, capacity-building activities, and continuous facilitation. The program involved community members, village officials, lecturers, and university students in collaborative learning and advocacy processes. Data were collected through field observations, focus group discussions, interviews, and participatory evaluations. The results indicate that the establishment of the Dua Boccoe Mandiri Group significantly enhanced citizens’ understanding of village planning mechanisms and increased their involvement in deliberative forums. Training activities improved villagers’ abilities to formulate development proposals and monitor budget implementation, while fostering greater transparency and responsiveness among village authorities. Nevertheless, several structural challenges, including inadequate infrastructure, limited telecommunications access, and uneven public information dissemination, continue to constrain broader participation. The findings demonstrate that community empowerment through education, facilitation, and collaborative governance can transform passive citizens into active stakeholders in local development. The experience of Desa Dua Boccoe highlights the importance of strengthening both human resource capacities and supporting infrastructure to achieve inclusive, transparent, and sustainable village governance. This model may serve as a reference for other rural communities facing similar challenges in promoting participatory democracy and community-based development